Alone in the sustainable wilderness; transforming sustainable competences and didactics in a design for change education - Østergaard, Thomas (Design and Technology Education: An International Journal, 2021)
According to UNESCO (2012) pedagogies associated with Educations for Sustainable Development (ESD) should spur and inspire students to think critically, ask questions and reflect. The assumption is, that pedagogies are moving towards student-centred participatory learning. Still, the educator is at the core of the transition towards developing ESD’s, so changes of the educators’ worldviews and practices are emerging. The educators’ competences and knowledge on ESD-development becomes central as the question of the what and the how the students are taught becomes more pressing. Today many sustainable educations still have a high focus on systemic issues (external systems); politics, technology, or socioeconomic structures (Parodi & Tamm, 2018, Wamsler, 2019) and lately the UNESCO (2021) has stressed the need for adapting cognitive, transformative, personal, emotional, dimensions of learning into ESD. In a transformative learning setting the educators should provide real-heartfelt experiences generating the students with capacities to reflect critically on both systems and personal design practice methods and help them aligning their methods with their personal emotional values. In doing so, the educators feel left “alone in the Wilderness” and research in the personal dimension of sustainable transformation and connection of this to ESD’s is scarce (Parodi & Tamm, 2018, Wamsler, 2019). On this backdrop, this article provides a reflexive case study of a BA level course on “Design for Change” performed from 2019 – 2021 using transformative learning practices and the connected interventions in the form of a reflection tool, the Decoding Creativity Tool (DCT). The data was collected to discover if and how the students could enhance personal sustainable competences using transformative learning focusing on the personal emotional and creative development and awareness, reflection tools and “visiting” methods. Implementing transformative learning and ESD’s into educational practices requires radical revisions of the design education system, managerial strategic commitment and involves many levels of the HE’s. It requires both internal and external collaborations for the design educations and could involve developing new didactics and methods where ideas can grow. (Barth & Rieckmann, 2012).